Cogenerative PV thermal modules of different design for autonomous heat and electricity supply - Kharchenko, V. (IGI Global, 2018)
Solar energy is used for electricity production by means of photovoltaic modules and for heat supply by means of solar water-heating collectors. In recent years, combined cogeneration photovoltaic thermal modules which work out at the same time both electricity and thermal energy began to be applied actively. The chapter includes consideration of the main types of cogenerative photovoltaic thermal modules of different design such as planar liquid devices as well as devices with concentrator of solar radiation. The advantages and disadvantages of each type are presented. Main directions for improving the efficiency of converting solar energy into thermal and electricity are offered. The description of the offered construction of the module, and also results of theoretical and pilot studies of the module is provided in full-scale conditions. Installation for such tests is described as well. Testing photovoltaic thermal modules with planar and concentrator design are presented in the chapter. Â© 2018, IGI Global. All rights reserved.